Environmental fragility of Iguaçu river watershed, Paraná, Brazil - Dalla Corte, Ana Paula; Klein Hentz, Ângela Maria; Doubrawa, Betina; Sanquetta, Carlos Roberto (Bosque (Valdivia), 2017)
The aim of this study was to analyze the environmental fragility of Iguaçu River watershed, Paraná. Regarding fragility potential, most watersheds fell under the moderate fragility class (40.47 % of the total), followed by very low (18.83 %), low (16.20 %), high (13.27 %) and very high with only 8.68 %. Concerning emerging fragility, most watersheds again lay within moderate fragility (41.55 %), though in this case low fragility was found in second place (with 40.73 %), followed by very low (7.67 %), high (6.50 %) and very high (0.99 %). Urban areas corresponded to 1.37 % and bodies of water to 1.18 % of the area. From a visual analysis, emerging fragility was observed to be high and very high, when present, followed by flooded areas; thus, demonstrating the importance of considering them in such studies, since they are environments with very unstable structural features including certain soil types, significant erosion from water, among others. The results of certain classes also appeared to depend on the weights given to factors considered as affecting the outcome. When the mean fragility methodology was used, the classes tended to follow a normal distribution, i.e. with a dominant moderate class. Therefore one can conclude that determining the importance of each factor is essential in evaluating environmental fragility, and therefore, weights should be carefully defined for each situation.